Development of Central Javanese Ethnomathematics-Based E-Learning Materials to Enhance Students’ Learning Interest and High-Order Thinking Skills - Esti Ayu Ratnasari; Nursiwi Nugraheni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop educational materials rooted in Central Javanese culture and based on indigenous mathematics, with a view to stimulating students’ interest in learning and fostering their higher-order thinking skills. This study adopts a research and development method based on the Borg and Gall model, modified into eight stages: identification of potential issues, data collection, product design, design validation, design revision, product trialing, product revision, and user trialing. The research utilized a two-group pretest-posttest design comparing a control class and an experimental class. Data analysis techniques included the paired-sample t-test, independent-sample t-test, and N-gain analysis. Several experts conducted product validation. The validation results from the content expert yielded a score of 95.83% (highly acceptable), the media expert scored 93.75% (highly acceptable), and the language expert scored 94.79% (highly acceptable). The practicality test of the teaching materials among students yielded a score of 98.3% in the control group and 99.2% in the experimental group, indicating high practicality. Meanwhile, the practicality test by teachers in the control group and the experimental class each yielded a score of’100%, indicating high practicality. The independent sample t-test showed a statistically significant difference in student’s learning interest between the experimental and control groups (sig < 0,05), with N-Gain score of 0,60 for experimental group and 0,38 for control group. Similarly, a statistically significant difference was found in students’ higher-order thinking skills between the two groups (sig < 0,05), with n-Gain scores of 0,61 for experimental group and 0,38 for the control group. This study demonstrates that applying ethnomathematics-assisted learning to the multiplication and division of decimal numbers can enhance interest in learning and higher-order thinking skills. This study concludes that the developed teaching materials meet high standards in both effectiveness and practicality, making them a viable option for mathematics instruction at the elementary school level.